The impact of MGNREGS on child labour and child education: an empirical analysis. Issue 3 (3rd April 2019) - Das, Saswati; Mukherjee, Diganta
ABSTRACT: This article addresses the persistent claim that the Mahatma Gandhi National Rural Employment Guarantee Scheme (MGNREGS) has a negative impact on the availability of labour for agricultural operations, which has significant implications for the induced demand for child labour as a cheaper substitute for unskilled adult labour on agricultural farms in peak seasons. The study contributes to this debate by examining three issues: (i) effects of seasonality on child intensity of labour; (ii) impact of MGNREGS on child intensity of labour; and (iii) impact of seasonality and MGNREGS on human capital formation.